Traffic Noise: A Silent Killer of Male Gamate of Albino Rats - Purushottam Pramanik , Snehangshu Biswas (Al Ameen Medical College, 2012)
Objectives: The study aims to estimate the change in the weight of testis, sperm count, sperm morphology, testicular cholesterol and protein level in acute and chronic traffic noise exposed albino rats. Background: Road traffic is a significant source of noise pollution, a type of environmental stress. Traffic noise significantly increases adrenal cortical function and causes testicular dysfunction. Method: Experiment was performed on adult male albino rats. Animals were divided in to one control group and two experimental groups. Both the experimental groups were exposed to traffic noise having intensity 80 dB to 90 dB at the rate of 5 hr daily and control group was not exposed. First experimental group was exposed to traffic noise for 30 days and second group for 60 days. Testicular weight, sperm count, sperm morphology, testicular protein level and testicular cholesterol level were estimated. Statistical analysis was done using unpaired 't' test. Result: Contribution of testis to body weight, testicular protein level and sperm count were low but testicular cholesterol level was more in traffic noise exposed rats than unexposed counterpart. Traffic noise exposure also increased percentage of morphologically abnormal sperm. Conclusion: Traffic noise adversely affect male gamete and such effect may be due to noise-induced suppression of testosterone synthesis.